Tax Avoidance In Corporations: The Influence Of Managerial Ability, Gender Diversity, And Director Age With Audit Quality Moderation. - Injilia, Dian Kristi (Lembaga Penerbit Fakultas Ekonomi dan Bisns, Universitas Trisakti, 2022)
This study investigates the impact of managerial power, gender diversity in the boardroom, and director age on tax avoidance in publicly listed manufacturing companies in Indonesia, with a focus on the moderating role of audit quality. Despite the importance of understanding tax avoidance within corporate governance, research on how these factors interact in a developing economy context remains limited. Using data from 73 manufacturing firms listed on the Indonesia Stock Exchange between 2014 and 2017, this quantitative study employs multiple regression analysis to assess these relationships. The results indicate that managerial power significantly reduces tax avoidance, as capable managers prefer to enhance firm value through efficient operations rather than aggressive tax strategies. While female directors do not significantly influence tax avoidance, possibly due to underrepresentation, older directors are found to be more conservative, reducing the likelihood of engaging in tax avoidance. Interestingly, audit quality does not consistently moderate the effects of these variables on tax avoidance. These findings underscore the importance of managerial capabilities and demographic diversity in reducing tax avoidance and highlight the need for improved corporate governance practices.